Скарби бронзових прутків Середнього Поросся - Романюк, В.В. (Археологія і давня історія України, 2019)
У статті розглянуті знахідки, які свідчать
про розвинене бронзоливарне виробництво на поселенських пам'ятках скіфської доби в Пороссі. In the article the noticeable role of bronzocasting
production is considered on the settler monuments of
scythian time in the Tarashchanskiy district of the
Kyiv area.
Among the numerous testimonies of bronze casting
production and trade in metals the two most interesting
items are bronze treasures, recently discovered in
the villages of Lisovichi and Dibrovka in Kyiv region.
Each contained about 300 bars with a length of 40.5
and 22 cm (Lisovichi), 41 cm (Dibrovka), total weight
about 30 kg. We can assume a different purpose of bronze bars: blanks for specific products, raw materials
for smelting, the equivalent of money. Spectral analysis of the products showed that they are made of
high-quality tin bronze with a high admixture of iron (2.58 %, Lisovichi). Titanium content (4.39 %, Lisovichi)
remains unclear (is it a natural impurity in raw materials?) According to the place of discovery (on settlements),
treasures of bars can be dated to Scythian time (the end of 6th—5th century BC?), although more late dates are not excluded.